Evaluation of ThyroSeq v2 performance in thyroid nodules with indeterminate cytology. Issue 3 (March 2017) - Valderrabano, Pablo; Khazai, Laila; Leon, Marino E; Thompson, Zachary J; Ma, Zhenjun; Chung, Christine H; Hallanger-Johnson, Julie E; Otto, Kristen J; Rogers, Kara D; Centeno, Barbara A; McIver, Bryan
Abstract : ThyroSeq v2 claims high positive (PPV) and negative (NPV) predictive values in a wide range of pretest risks of malignancy in indeterminate thyroid nodules (ITNs) (categories B-III and B-IV of the Bethesda system). We evaluated ThyroSeq v2 performance in a cohort of patients with ITNs seen at our Academic Cancer Center from September 2014 to April 2016, in light of the new diagnostic criteria for non-invasive follicular thyroid neoplasm with papillary-like nuclear features (NIFTP). Our study included 182 patients (76% female) with 190 ITNs consecutively tested with ThyroSeq v2. Patient treatment followed our institutional thyroid nodule clinical pathway. Histologies of nodules with follicular variant papillary thyroid carcinoma or NIFTP diagnoses were reviewed, with reviewers blinded to molecular results. ThyroSeq v2 performance was calculated in nodules with histological confirmation. We identified a mutation in 24% ( n =  45) of the nodules. Mutations in RAS were the most prevalent ( n =  21), but the positive predictive value of this mutation was much lower (31%) than that in prior reports. In 102 resected ITNs, ThyroSeq v2 performance was as follows: sensitivity 70% (46–88), specificity 77% (66–85), PPV 42% (25–61) and NPV 91% (82–97). The performance in B-IV nodules was significantly better than that in B-III nodules (area under the curve 0.84 vs 0.57, respectively; P  = 0.03), where it was uninformative. Further studies evaluating ThyroSeq v2 performance are needed, particularly in B-III.